Green Tea Yoghurt with Encapsulated Lacticaseibacillus paracasei E1 Improves Hepatocyte Damage in High-Fat High-Fructose Diet Mice by Reducing MDA and Increasing SOD - Fadlilah, Dawama Nur; Izati, Rahmi; Al Faizah, Belinda Nabiila; Kavitarna, Septhyanti Aprilia; Ardiansyah, Esha; Sa'adah, Nur Alfi Maghfirotus; Atho'illah, Mochammad Fitri; Arifah, Siti Nur; Soewondo, Aris; Jatmiko, Yoga Dwi; Wardhani, Shinta Oktya; Barlianto, Wisnu; Rifa'i, Muhaimin (Cell and BioPharmaceutical Institute, 2024)
Background: Obesity is a global epidemic caused by excessive body fat, which is increasing free fatty acids in the liver, causing oxidative stress and liver cell damage. Green tea yogurt (GTY) with encapsulated Lacticaseibacillus paracasei E1 (GTY-LpE1) might have a beneficial effect in reducing liver cell damage. This study was conducted determine GTY-LpE1 effect on superoxide dismutase (SOD) expression, malondialdehyde (MDA) expression and liver histopathology in high-fat high-fructose diet (HFFD) mice. Material and Methods: A completely randomized design (CRD) with 7 groups, including normal diet (ND) group, HFFD group, 1.3 mg/kg BW simvastatin (SIM)-administered HFFD group, 5 g/kg BW probiotic yoghurt (PY)-administered HFFD (PY), 2.5 g/kg BW GTY-administered HFFD (2.5 GTY), 5 g/kg BW GTY-administered HFFD (5 GTY), and 10 g/kg BW GTY-administered HFFD (10 GTY). The diet was given for 16 weeks, followed by oral administration of sim/yoghurt during the last 4 weeks. Mice were sacrificed and the liver was collected. SOD and MDA expression were analyzed by flow cytometry. Histopathology analysis was done by evaluating hematoxylin-eosin (HE) staining of the liver.Result: The percentage of necrotic cells were 34.55, 34.31, and 21.95%, when treated with 2.5, 5, and 10 g/kg BW with GTY-administered HFFD, respectively, these were lower than the ones in the HFFD group (69.49%). The percentage of MDA expression were 15.55, 18.69, and 22.42%, respectively, these were lower than the ones in the HFFD group as well. The percentage of SOD expression were 9.49, 7.85, and 11.11%, respectively, these were higher than the ones in the HFFD group (3.44%). Conclusion: GTY-LpE1 could decrease the number of necrotic cells in the HFFD mice livers and improve the hepatocyte damage by reducing MDA expression and enhancing SOD expression. GTY-LpE1 can be used as an alternative food to control obesity.Keywords: alginate, chitosan, encapsulation, green tea, probiotic